THE INFLUENCE OF GADGET USE ON ADOLESCENT SOCIAL INTERACTION IN BANYUMAS VILLAGE - Pratiwi, Indah; Erlina, Leni; Sitepu, Melyani Sari (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study was to determine the effect of using Gadgets on social interaction among adolescents in Banyumas Village. The methodology used in this study uses a descriptive qualitative approach. The sample respondents in this study were 54 adolescents, consisting of 45 female adolescents and 9 male adolescents. Based on the findings of the research results, it was found that there were positive and negative impacts on the use of gadgets on adolescents in Banyumas Village. The positive impact of using gadgets includes; making it easier for teenagers to establish communication with people who are far away, and making it easier for teenagers to get information about education quickly. The negative impacts of using gadgets include; Adolescents experiencing social dysfunction, the intensity of direct interaction with other humans being reduced, adolescenbeingare less sensitive to their surroundings, the quality of direct interaction being very low, adolescents rarely communicating directly (face to face) and adolescents become consumptive. However, the form of interaction that takes place between adolescents tends to be associative, meaning that adolescents use telecommunication gadgets to collaborate with other humans by forming groups on chat media and social media, the main purpose of forming these groups is to disseminate information.